Potenciales evocados I: Introducción - Muñoz Gamboa, Caupolicán; Jiménez Cruz, Joel (Revista Mexicana de Ingenieria Biomedica, 2001)
Brain electrical responses known as evoked potentials (PE), which are obtained from controlled sensorial stimulation as a component part of the electroencephalograph signals (EEG), are presented in an introductory manner in this paper. PE’s permit to understand the way the information processing is carried out by the nervous system, reason by what it is convenient to know and emphasize some of their most important properties.